Self-compassion as a mediator of attachment anxiety, attachment avoidance, and complex PTSD in college students with adverse childhood experiences - Yu Peng; Zahari Ishak (Scientific Reports)
Abstract Given the significant prevalence of adverse childhood experiences (ACEs) and their detrimental impact on mental health, this study examines the relationship between attachment anxiety, attachment avoidance, and complex post-traumatic stress disorder (CPTSD) among college students with ACEs, emphasizing the mediating role of self-compassion (SC). A sample of 32,388 students from Kunming, China completed a survey including the Revised Adverse Childhood Experiences Questionnaire (ACEQ-R), the Adult Attachment Scale (AAS), the International Trauma Questionnaire (ITQ), and the Self-Compassion Scale-Short Form (SCS-SF). Among the participants, 3,896 reported at least one ACE. Data were analyzed using structural equation modeling (SEM) to explore the proposed mediation model. Results revealed that both attachment anxiety and avoidance positively influenced CPTSD symptoms while negatively affecting SC. SC negatively influenced CPTSD symptoms, acting as a significant mediator. The mediating effect of SC was stronger for disturbances in self-organization (DSO) than for post-traumatic stress disorder (PTSD) symptoms. These findings underscore the importance of fostering SC in interventions aimed at mitigating the influence of attachment anxiety and avoidance on CPTSD among college students with ACEs.